BRICS Countries Energy Cooperation. Significance of the Issue - M. O. Ryazanova (Vestnik MGIMO-Universiteta)
The article studies one of the key spheres of BRICS framework - energy security. Given the recent decline of economic growth rates in BRICS countries, highlighting of such areas as infrastructural funding and establishing of effective international financial regulatory institutions, beneficial cooperation in energy sector despite its importance for the national interests of member states, nowadays perspectives of BRICS cooperation in energy security seem to be unclear for the leading researchers and analysts. The article contemplates the evolution of energy cooperation issue in the context of BRICS summits. Besides,proceeding from the classification of energy resources into two groups - traditional ones and eco-fuels - the analysis helps to determine potential ways of interaction within the member states taking into account bothmotivating and constraining factors. However, notwithstanding the possibility of the intergroup multilateralrelations in this sphere and overall strengthening of economic ties among the members, the BRICS energy cooperation iscurrently of bilateral and unequally developed nature, which is determined by a number of historically formed circumstances and national interests.